ASSOCIATION OF ARTERIAL HYPERTENSION AND BLOOD PRESSURE WITH MORTALITY AMONG POPULATION AGED 55 YEARS AND OLDER, ACCORDING TO ANTIHYPERTENSIVE TREATMENT. (April 2021) - Imaeva, Asiia; Shalnova, Svetlana; Balanova, Yulia; Kapustina, Anna; Shkolnikov, Vladimir
Abstract : Objective: Objective: to evaluate relationship of arterial hypertension (AH), elevated blood pressure (BP) and all-cause and cardiovascular disease (CVD) mortality among Muscovites aged 55 years and older according to antihypertensive therapy. Design and method: Methods: data of 1876 Muscovites 55 years and older (47.9% males) from the prospective population-based cohort study named the Stress, Aging and Health in Russia (SAHR) was used. The elevated BP was defined as BP > = 140/90 mmHg. AH was diagnosed according to European Society of Cardiology Guidelines. The treatment of hypertension was defined as the current use of a prescribed medication intended to lower BP, the effective treatment – as the presence of SBP < 140 mmHg and DBP <90 mmHg among treated participants. During the follow-up period (mean – 8, 5 years) 547 deaths, including 330 from CVD, were identified. Hazard proportional risk model (Cox) was applied for hazard risks (HR) evaluation with 95%CI. Results: Results: the prevalence of AH and elevated blood pressure was 73, 9% and 53, 4%, respectively. After adjusting for age and sex AH had no significant associations with all-cause and CVD mortality (HR = 1, 2; 95% CI: 0, 98–1, 5; p = 0, 07; HR = 1, 24; 95% CI: 0, 94–1, 64; p = 0, 1). Whereas elevated BP was significantly associated with all-cause and CVD mortality (HR = 1, 31; 95% CI: 1, 10–1, 55; p = 0, 003, HR = 1, 40; 95% CI: 1, 12–1, 75; p = 0, 004). Moreover there was the strong contribution of elevated BP to all-cause mortality (HR = 1, 39; 95% CI: 1, 10–1, 77; p = 0, 006) and CVD mortality (HR = 1, 55; 95% CI: 1, 14–2, 10; p = 0, 005) among those who received antihypertensive therapy after adjustment to sex and age. Receiving antihypertensive therapy had no associations with all-cause and CVD mortality (p > 0, 05). At the same time, the effective antihypertensive therapy reduced risk of all-cause and CVD mortality by 28% and 35%, respectively (HR = 0, 72; 95% CI: 0, 57–0, 91; p = 0, 006; HR = 0, 65; 95% CI: 0, 48–0, 88; p = 0, 005). Conclusions: Although AH is an important risk factor of CVD, among population aged 55 years and older only the elevated levels of BP and antihypertensive therapy efficacy were associated with all-cause and CVD mortality.